Luminescent Imidazo[1,5‐a]pyridine Scaffold: Synthetic Heterocyclization Strategies‐Overview and Promising Applications - Volpi, Giorgio (Asian journal of organic chemistry, 2022)
In the last few years, imidazo[1,5‐a]pyridine derivatives have attracted growing attention due to their remarkable emissive behaviours, structural modification and biological properties. Previously published works emphasize the possible technological applications of this luminescent scaffold and demonstrate the stringent relationship between chemical substituents and optical properties. The main goal of this work is to provide a complete list of the reported achievements concerning these promising heterocyclization reactions obtained starting from a huge variety of reagents, catalysts, oxidants, dehydrating agents involved in various reaction conditions. Particular attention is focused on the final possible substitutions, conjugations and structural modifications of the reported synthetic approaches, a powerful aspect to design innovative and employable new luminescent imidazo[1,5‐a]pyridine products. The main goal of this review is to provide a complete list of the reported achievements concerning the heterocyclization reactions to obtain imidazo[1,5‐a]pyridine derivatives starting from a huge variety of reagents, catalysts, oxidants, dehydrating agents involved in various reaction conditions. Particular attention is focused on the final possible substitutions and structural modifications of the reported synthetic approaches, a powerful aspect to design innovative emitters.